How (Not) to Theologize Psychological Distress: Lessons from Thinking Across Conditions - Jessica Coblentz (Journal of Moral Theology)
With appreciation for how Stephanie Edwards and Catherine Yanko apply insights from Coblentz’s _Dust in the Blood: A Theology of Life with Depression_ to theologies focused on other forms of psychological distress, Coblentz elucidates from their essays six insights or “lessons” to apply to the ongoing work of theologizing psychological distress. These lessons variously explore the relationship of different mental health conditions, mental health stigma, social dimensions of psychological distress, complexities of moral agency, epistemic injustice, and the place of Christ in the ongoing project of theologizing mental health.